2021
DOI: 10.1002/joa3.12623
|View full text |Cite
|
Sign up to set email alerts
|

QT interval and repolarization dispersion changes during the administration of hydroxychloroquine/chloroquine with/without azithromycin in early COVID 19 pandemic: A prospective observational study from two academic hospitals in Indonesia

Abstract: Background Hydroxychloroquine/chloroquine (HCQ/CQ) treatment for COVID‐19 was associated with QT interval prolongation and arrhythmia risks. This study aimed to investigate QTc interval and ventricular repolarization dispersion changes, as markers of arrhythmia risks, after HCQ/CQ administration with/without azithromycin (AZT) during COVID‐19 pandemic. Methods A prospective observational study was performed in two academic hospitals in Indonesia. Adult patients who received HCQ/CQ alone and HCQ/CQ + AZT concom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…These results may aid in early diagnosis in the clinical setting. Now, in the COVID‐19 era, 27 , 28 in the future, these findings, combined with BNP levels, will contribute to establishing a clinical scoring system.…”
Section: Discussionmentioning
confidence: 99%
“…These results may aid in early diagnosis in the clinical setting. Now, in the COVID‐19 era, 27 , 28 in the future, these findings, combined with BNP levels, will contribute to establishing a clinical scoring system.…”
Section: Discussionmentioning
confidence: 99%
“…The median QTc observed at the CHUL could reflect a greater sensitivity of this population to treatment. Some authors showed that cardiac arrythmias in COVID-19 patients with severe or critical disease or with myocardial impact also involve QTc prolongation, while others found that QTc prolongation is rare during COVID-19 but drugs like HCQ and azithromycin are associated with a significant risk of QTc prolongation in SARS-CoV2 infected persons; this risk increases when azithromycin is associated with HCQ [ 23 , 24 , 25 ]. Additionally, COVID-19 patients were shown to be more susceptible to drug-induced QTc prolongation [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…As concentrações sob o regime de dosagem atualmente recomendado estão abaixo da margem de segurança para efeitos colaterais, o que sugere que esses regimes de dosagem são geralmente seguros (Meo et al, 2020) Relatar as características biológicas, moleculares, farmacológicas e clínicas da cloroquina e hidroxicloroquina para o tratamento da COVID-19 Não foram encontradas evidências claras de benefícios da terapia com cloroquina para a infecção ambulatorial inicial ou para a profilaxia (Das et al, 2020) Avaliar Autores (Axfors et al, 2021;Das et al, 2020;Ferreira et al, 2023;Gumilang et al, 2021;Kashour et al, 2021;Meo et al, 2020;Nicol et al, 2020;Tleyjeh et al, 2021;Yao et al, 2021) Farmacocinética -Dose única: 155 mg de hidroxicloroquina e 300 mg ou 600 mg de cloroquina; Não se investigou: parâmetros de exposição, tempo para atingir a concentração sérica máxima e interação com alimentos na absorção; -Distribuição: concentrada nas hemácias, com ligação média a proteínas plasmáticas de 59% (30 a 50% para a hidroxicloroquina), além de baço, pulmões, rins e fígado; -Metabolização: hepática; -Eliminação: renal de 30 a 60 dias.…”
Section: Autoriaunclassified